Data for: First Report of the Occurrence of Trichinella-Specific Antibodies in Domestic Pigs in Central and Eastern Uganda - Roesel, Kristina; Nöckler, Karsten; Baumann, Maximilian P.O.; Fries, Reinhard; Dione, Michel M.; Clausen, Peter-Henning (International Livestock Research Institute, 2016)
The dataset contains the basic underlying information for the manuscript "First Report of the Occurrence of Trichinella-specific Antibodies in Domestic Pigs in Central and Eastern Uganda". Sheet 1 includes the lab data (serology), sheet 2 the lab data and related metadata for descriptive analysis, and sheet 3 the results of the digestion assay (all negative).